Recognition of a Single Transmembrane Degron by Sequential Quality Control Checkpoints - Fayadat, Laurence; Kopito, Ron R. (Molecular biology of the cell, 2003)
To understand the relationship between conformational maturation and quality control–mediated proteolysis in the secretory pathway, we engineered the well-characterized degron from the α-subunit of the T-cell antigen receptor (TCRα) into the α-helical transmembrane domain of homotrimeric type I integral membrane protein, influenza hemagglutinin (HA). Although the membrane degron does not appear to interfere with acquisition of native secondary structure, as assessed by the formation of native intrachain disulfide bonds, only ∼50% of nascent mutant HA chains (HA ++ ) become membrane-integrated and acquire complex N-linked glycans indicative of transit to a post-ER compartment. The remaining ∼50% of nascent HA ++ chains fail to integrate into the lipid bilayer and are subject to proteasome-dependent degradation. Site-specific cleavage by extracellular trypsin and reactivity with conformation-specific monoclonal antibodies indicate that membrane-integrated HA ++ molecules are able to mature to the plasma membrane with a conformation indistinguishable from that of HA wt . These apparently native HA ++ molecules are, nevertheless, rapidly degraded by a process that is insensitive to proteasome inhibitors but blocked by lysosomotropic amines. These data suggest the existence in the secretory pathway of at least two sequential quality control checkpoints that recognize the same transmembrane degron, thereby ensuring the fidelity of protein deployment to the plasma membrane.